A molecular sponge that exclusively adsorbs acetonitrile. Issue 16 (27th March 2023) - Habata, Yoichi; Wada, Ayumi; Lee, Eunji; Ju, Huieyong; Yoshiba, Yuki; Horita, Hiroki; Ishii, Jun-ichi; Ikeda, Mari; Kuwahara, Shunsuke
Abstract : A tetra-armed cyclen (L ) with phenylethynylmethyl groups as side-arms forms L ·CH3 CN inclusion crystals from acetonitrile–organic mixed solvents with high selectivity. Abstract : We report that a tetra-armed cyclen (L ) with phenylethynylmethyl (Ph–CC–CH2 –) groups as side-arms forms L ·CH3 CN (L ·AN ) inclusion crystals from acetonitrile–organic mixed solvents with high selectivity and acts as if it is an acetonitrile selective molecular sponge.